SF6 switchgear - Ryan, H. M. (Hugh McLaren); Jones, G. R. 1938- (Gordon Rees) (P. Peregrinus on behalf of the Institution of Electrical Engineers, 1989)
An extensive review of developments in SF6 switchgear covering fundamental properties of SF6, interrupter types, characteristics and associated operating mechanisms, arc modelling and computer aided methods for interrupter design and evaluation.